The prevalence and treatment patterns of familial hypercholesterolemia among Thai patients with premature coronary artery disease. Issue 4 (19th May 2023) - Nawaka, Nantiya; Rattanawan, Chutima; Pussadhamma, Burabha; Wutthimanop, Atthakorn; Nuinoon, Manit; Porntadavity, Sureerut; Theansun, Watcharinthon; Jeenduang, Nutjaree
ABSTRACT: Objectives: Familial hypercholesterolemia (FH) is an autosomal dominant genetic disorder that is characterized by severe hypercholesterolemia. The prevalence of FH in Thailand has not been reported. Therefore, this study aimed to investigate the prevalence of FH and treatment patterns among Thai patients with premature coronary artery disease (pCAD). Methods: A total of 1, 180 pCAD patients at two heart centers from northeastern and southern Thailand between October 2018 and September 2020 were enrolled. FH was diagnosed using the Dutch Lipid Clinic Network (DLCN) criteria. pCAD was diagnosed in men aged < 55 years and women aged < 60 years. Results: The prevalence of definite/probable FH, possible FH, and unlikely FH in pCAD patients was 1.36% (n = 16), 24.83% (n = 293), and 73.81% (n = 871), respectively. Definite/probable FH in pCAD patients had a significantly higher frequency of STEMI but a lower frequency of hypertension than those with unlikely FH. After discharge, most pCAD patients (95.51%) received statin therapy. Definite/probable FH patients had a higher frequency of high-intensity statin therapy than those with possible FH and unlikely FH. After follow-up for 3–6 months, approximately 54.72% of pCAD patients with DLCN scores ≥ 5 had a reduction in LDL-C > 50% from baseline. Conclusions: The prevalence of definite/probable FH, particularly possible FH, was high among pCAD patients in this study. The early diagnosis of FH among Thai pCAD patients should be performed for the early treatment and prevention of CAD.